The risk of uterine rupture is not increased with single‐ compared with double‐layer closure: a Swedish cohort study. (4th August 2014) - Hesselman, S; Högberg, U; Ekholm‐Selling, K; Råssjö, E‐B; Jonsson, M
<x xml:space="preserve">Abstract</x> Objective To compare single‐ with double‐layer closure of the uterus for the risk of uterine rupture in women attempting vaginal birth after one prior caesarean delivery. Design Cohort study. Setting Sweden. Population From a total of 19 604 nulliparous women delivered by caesarean section in the years 2001–2007, 7683 women attempting vaginal birth in their second delivery were analysed. Methods Data from population‐based registers were linked to hospital‐based registers that held data from maternity and delivery records. Logistic regression was used to estimate the risk of uterine rupture after single‐ or double‐layer closure of the uterus. Results are presented as odds ratios (ORs) with 95% confidence intervals (95% CIs). Main outcome measure Uterine rupture. Results Uterine rupture during labour occurred in 103 (1.3%) women. There was no increased risk of uterine rupture when single‐ was compared with double‐layer closure of the uterus (OR 1.17; 95% CI 0.78–1.76). Maternal factors associated with uterine rupture were: age ≥35 years and height ≤160 cm. Factors from the first delivery associated with uterine rupture in a subsequent delivery were: infection and giving birth to an infant large for gestational age. Risk factors from the second delivery were induction of labour, use of epidural analgesia, and a birthweight of ≥4500 g. Conclusions There was no significant difference in the rate of uterine rupture when single‐layer closure was compared with double ‐layer closure of the uterus.